Mutations found in the Asc1 gene that confer susceptibility to the AAL-Toxin in ancestral tomatoes from Peru and Mexico - Tsuzuki, Rin (2020)
Tomato susceptibility/resistance to stem canker disease caused by Alternaria alternata f. sp. lycopersici and its pathogenic factor AAL-toxin is determined by the presence of the Asc1 gene. Several cultivars of commercial tomato (Solanum lycopersicum var. lycopersicum, SLL) are reported to have a mutation in Asc1, resulting in their susceptibility to AAL-toxin. We evaluated 119 ancestral tomato accessions including S. pimpinellifolium (SP), S. lycopersicum var. cerasiforme (SLC) and S. lycopersicum var. lycopersicum “jitomate criollo” (SLJ) for AAL-toxin susceptibility. Three accessions, SP PER018805, SLC PER018894, and SLJ M5-3, were susceptible to AAL-toxin. SLC PER018894 and SLJ M5-3 had a two-nucleotide deletion (nt 854_855del) in Asc1 identical to that found in SLL cv. Aichi-first. Another mutation (nt 931_932insT) that may confer AAL-toxin susceptibility was identified in SP PER018805. In the phylogenetic tree based on the 18 COSII sequences, a clade (S3) is composed of SP, including the AAL-toxin susceptible PER018805, and SLC. AAL-toxin susceptible SLC PER018894 and SLJ M5-3 were in Clade S2 with SLL cultivars. As SLC is thought to be the ancestor of SLL, and SLJ is an intermediate tomato between SLC and SLL, Asc1s with/without the mutation seem to have been inherited throughout the history of tomato domestication and breeding.